Marijuana boom: the rise and fall of Colombia's first drug paradise - Britto, Lina (University of California Press, 2020)
Introduction : a forgotten history -- Wheels of progress : tropical commodities and regional formation -- Coming from the mountain : coffee contraband and marijuana smuggling -- Santa Marta gold : technological adaptations and boom -- Parranderos : Vallenato music and cultural negotiations -- Two peninsulas : Narcotics diplomacy and the war on drugs -- Reign of terror : criminalization and violence -- Conclusions : a remembered history